2022
DOI: 10.1101/2022.12.15.520602
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Explicit and implicit motor simulations are impaired in individuals with aphantasia

Abstract: Individuals with aphantasia report having difficulties or an inability to generate visual images of objects or events. So far, there is no evidence showing that this condition also impacts the motor system and the generation of motor simulations. We probed the neurophysiological marker of aphantasia during explicit and implicit forms of motor simulation, i.e., motor imagery and action observation, respectively. We tested a group of individuals without any reported imagery deficits (phantasics) as well as a gro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…While the questions of mental imagery in animals currently appears largely intractable to convincing empirical validation, a phenomenon in humans referred to as aphantasia , i.e., the inability to engage in mental imagery ( Dance et al, 2022 ), provides an interesting opportunity to discover more about how mental imagery contributes to our motor and perceptual processing on the neurophysiological level. This field is still in its infancy, but some early studies suggest that motor simulations may indeed be impaired in individuals with aphantasia ( Dupont et al, 2022 ), who also present with measurable alterations in behavioral and neural signatures during mental imagery ( Milton et al, 2021 ; Dupont et al, 2022 ).…”
Section: Structure and Function Of Distributed Brain Network For Moto...mentioning
confidence: 99%
“…While the questions of mental imagery in animals currently appears largely intractable to convincing empirical validation, a phenomenon in humans referred to as aphantasia , i.e., the inability to engage in mental imagery ( Dance et al, 2022 ), provides an interesting opportunity to discover more about how mental imagery contributes to our motor and perceptual processing on the neurophysiological level. This field is still in its infancy, but some early studies suggest that motor simulations may indeed be impaired in individuals with aphantasia ( Dupont et al, 2022 ), who also present with measurable alterations in behavioral and neural signatures during mental imagery ( Milton et al, 2021 ; Dupont et al, 2022 ).…”
Section: Structure and Function Of Distributed Brain Network For Moto...mentioning
confidence: 99%
“…Recent neuroimaging (Dupont et al, 2022) and pupillary response (Kay et al, 2022) studies further support this interpretation. Dupont et al (2022) demonstrated that while motor imagery and observation evoked similar brain activity in controls, individuals with aphantasia exhibited an opposite response, suggesting an absence of mental simulation. Kay et al (2022) found no pupillary dilation in aphantasia during visual imagery tasks, unlike controls, further corroborating the lack of imagery in aphantasia.…”
Section: Introductionmentioning
confidence: 86%
“…Dupont et al . 1 report the well-established effect that corticospinal excitability is facilitated by kinaesthetic imagery and action observation 3 in participants with typical imagery generation abilities. In contrast, however, these facilitation effects were not found in the participants reporting aphantasia, where corticospinal excitability was not facilitated by either the explicit (kinaesthetic imagery) or implicit (action observation) simulation of movement.…”
mentioning
confidence: 97%
“…The study by Dupont et al . 1 published in Brain Communications used single-pulse transcranial magnetic stimulation (TMS) to measure corticospinal excitability during visual imagery, kinaesthetic imagery and action observation of a pinch movement. Participants self-reported either typical imagery abilities or aphantasia (reduced or absent imagery abilities).…”
mentioning
confidence: 99%
See 1 more Smart Citation